2019
DOI: 10.1108/ijebr-07-2019-0436
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial self-efficacy and intentions

Abstract: Purpose Building on social career cognitive theory, the purpose of this paper is to investigate outcome expectations as a mediator and subjective norms as a moderator in the relationship between entrepreneurial self-efficacy and intentions. Design/methodology/approach Using a sample of 1,026 students from US public and private universities retrieved from the Entrepreneurship Education Project, this study tests a first-stage moderated mediation model in a two-step process. Findings Results show that entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 69 publications
3
69
0
12
Order By: Relevance
“…Second, the additions of sustainable self-efficacy and sustainable self-identity constructs have significantly improved the model predictive power, thus confirming model effectiveness in predicting SEI. Previous studies have provided supports regarding the effectiveness of self-efficacy predicting intentions (Wilson et al , 2007; Santos and Liguori, 2019). Similarly, the role of sustainable self-efficacy was found significant in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Second, the additions of sustainable self-efficacy and sustainable self-identity constructs have significantly improved the model predictive power, thus confirming model effectiveness in predicting SEI. Previous studies have provided supports regarding the effectiveness of self-efficacy predicting intentions (Wilson et al , 2007; Santos and Liguori, 2019). Similarly, the role of sustainable self-efficacy was found significant in this study.…”
Section: Discussionmentioning
confidence: 93%
“…It emerges from Figure 1 that the question on how to further develop the "through" mode (i.e., the know-why) yields inquiries on how to cope with attitudes. First, beyond Theory of Planned Behavior (Krueger & Carsrud, 1993), self-efficacy constructs (e.g., Piperopoulos & Dimov, 2015;Santos & Liguori, 2020;Winkler & Case, 2014) and entrepreneurial metaphors (Anderson et al, 2009), other belief structures and their impact on attitudes need to be explored. Second, in accordance with the structure of Figure 1C, the attitudes have to be examined, and possibly measured, not only after the completion of the program but also in its origin.…”
Section: Discussionmentioning
confidence: 99%
“…From the result, it is found that ISE is significantly affected by entrepreneurial self-efficacy. Entrepreneurial self-efficacy has been indicated in a number of studies (Bellò et al, 2018;Osiri et al, 2019;Santos and Liguori, 2019;Tsai et al, 2016;Zhao et al, 2005). Researchers have found that encouragement from educational institutions, particularly universities, encourages individual self-efficacy and strengthens intention towards entrepreneurship (Guerrero et al, 2016;Kazumi and Kawai, 2017).…”
Section: Discussionmentioning
confidence: 99%